Effects of breathing supplemental oxygen before progressive exercise in patients with chronic obstructive lung disease. - McKeon, J L (1988)
A study was carried out to determine whether supplemental oxygen before exercise would improve maximum exercise performance and relieve exertional dyspnoea in 20 patients with chronic obstructive lung disease (mean FEV1 0.79 l; forced vital capacity 2.30 l). Patients performed two progressive treadmill exercise tests to a symptom limited maximum, with at least 30 minutes rest between tests. They received compressed air or supplemental oxygen from nasal prongs for 10 minutes before exercise in a double blind randomised trial with a crossover design. Heart rate and breathlessness score on a visual analogue scale were compared between tests at 75% of the maximum distance walked in the compressed air test. The mean arterial oxygen saturation (SaO2) after oxygen (93%) was significantly higher than after compressed air (91%). There was no significant change, however, in maximum distance walked or maximum heart rate, or in the breathlessness score or heart rate at 75% of maximum distance walked. The study had a power of 93% for detecting an increase of 50 metres in maximum distance walked. There was an order effect, with better performance on the second test; but the magnitude of the difference was small. It is concluded that administration of supplemental oxygen sufficient to raise SaO2 above 90% for 10 minutes before exercise is unlikely to improve maximum exercise performance or breathlessness on exertion in patients with chronic obstructive lung disease.